2022
DOI: 10.3390/biomedicines10020252
|View full text |Cite
|
Sign up to set email alerts
|

Role of NLRP7 in Normal and Malignant Trophoblast Cells

Abstract: Gestational choriocarcinoma (CC) is an aggressive cancer that develops upon the occurrence of abnormal pregnancies such as Hydatidiform moles (HMs) or upon non-molar pregnancies. CC cells often metastasize in multiple organs and can cause maternal death. Recent studies have established an association between recurrent HMs and mutations in the Nlrp7 gene. NLRP7 is a member of a new family of proteins that contributes to innate immune processes. Depending on its level of expression, NLRP7 can function in an infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 80 publications
(139 reference statements)
0
9
0
Order By: Relevance
“…Early in the 1970s, Brewer et al 30 proposed that CC was correlated with some immunologic aspects. In recent years, accumulating data 11 , 12 have indicated the ubiquitous overexpression of NLRP7 and PD-L1 in GTN, including CC. NLRP7 contributed to protumoral activities in an inflammasome-independent manner, and its interaction with PD-L1 may play a vital role in immune tolerance and tumor development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early in the 1970s, Brewer et al 30 proposed that CC was correlated with some immunologic aspects. In recent years, accumulating data 11 , 12 have indicated the ubiquitous overexpression of NLRP7 and PD-L1 in GTN, including CC. NLRP7 contributed to protumoral activities in an inflammasome-independent manner, and its interaction with PD-L1 may play a vital role in immune tolerance and tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the tumor microenvironment has received remarkable attention in cancer research. 10 Increasing literatures 11 , 12 reported NOD-like receptor protein 7 (NLRP7), a member of the NLR, involved in the innate immune response and regulating the expression of programmed cell death-ligand 1 (PD-L1). As the master gene that contributes to trophoblast tumorigenesis, its abnormality facilitates the foundation of immunosuppressive microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have investigated the function of NLRP7 in pyroptosis. NLRP7 is overexpressed in gestational choriocarcinoma (CC) trophoblast cells and may function in an inflammasome-dependent or independent pathways [ 19 ]. In our observation, we found that NLRP7 was one of the pyroptosis-associated prognostic biomarkers in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Even though PHM and CHM are usually benign diseases, patients remain at risk of developing GC. This risk is much higher for patients with CHM (20%) [ 2 ] than for patients with PHM (1.5%) [ 1 , 3 ]. Recent studies have demonstrated that recessive mutations in the inflammatory protein NLRP7 (Nucleotide-binding oligomerization domain, leucine-rich repeat family, Pyrin domain containing 7) are the major cause of recurrent HM [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the levels of expression of NLRP7, two pathways have been proposed for its function [ 3 ]. While normal levels of NLRP7 have been associated with inflammasome activity, its overexpression has been proposed to function in an inflammasome-independent manner [ 19 ].…”
Section: Introductionmentioning
confidence: 99%